Estimasi Proporsi Anak Usia 3-4 Tahun yang Mengalami Hambatan Kesalahan Artikulasi di Kecamatan Jebres Surakarta - Gunawan Gunawan; Dodiet Aditya Setyawan; Setyadi Nugroho (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Articulation is one of the basic capital for speech and language. At approximately 8 years of age, children are able to pronounce all vowels, consonants, and double consonants are the last consonants in all articulation development that children have at 8 years old. In early childhood education students aged 3 to 4 years, they should be able to produce all sounds appropriate to their articulation development age. Therefore, if at that age children still experience articulation errors and do not receive proper detection, it is feared that they will become permanent articulation problems. In this regard, there is no definitive data on the number of children with articulation disorders in Indonesia. Therefore, research is needed to estimate the proportion of early childhood education students aged 3 to 4 years who have articulation errors. Objectives: The main objective of this study was to estimate the proportion of preschool children aged 3 to 4 years who have articulation errors in Jebres District, Surakarta City. Methods: This study used a survey method with a data analysis technique of estimating proportions at a 95% confidence level (α = 0.05). There was no intervention/treatment for respondents, and only one observation was conducted without follow-up. This study was conducted at the following preschool/kindergarten in Jebres District, Surakarta: Raudhatul Athfal Al Kautsar PAUD, AL Kautsar Foundation, Surakarta, Tegal Mulyo, RT 03, RW 04, Mojosongo, Jebres, Surakarta, using a purposive sampling technique. The instrument in this study consists of two devices, the instrument in this study is in the form of an Articulation Test in Children who have ISBN: 978-623-97054-4-2 2021 and HKI: EC00202134473, July 21 (2021).8 The author's work, this instrument consists of two devices, a test device book with user instructions, in which it is equipped with pictures of language sounds to be assessed, to motivate children and a form in the form of a response sheet consisting of test responses. Results: The test device book can be used by all children who will be tested, while the test response sheet is filled in by the examiner. This instrument is used to assess the possibilities of each child's speech results, namely normal, substitution, omission, distortion and addition. Conclusion: Based on the survey and data analysis at a confidence level of 95% (α = 0.05), the overall results of 25 samples were 5 students (20%) with an estimated proportion ranging from 12.00% <π <28.00%. PAUD students aged 3 to 4 years who have articulation/pronunciation errors of Indonesian phonemes. Reviewed by PAUD students who are male and female aged 3 to 4 years, the number is greater, namely 4 students (16%) with an estimate of 8.67% <π <23.33% compared to female students, namely 1 student (4%) with an estimate of 0.08% <π <7.29%. That of the 4 types of articulation errors, substitution errors are most often made by PAUD students aged 3 to 4 years, namely 3 students (12%) with an estimated proportion ranging from 5.50%. <π<18.50%. Furthermore, omissions were found in 1 student (4%) with an estimated proportion of 0.08% <π<7.29% and addition problems were found in 1 student (4%) and there were no articulation errors in the form of distortion. Therefore, the interpretation of the analysis results is that there are two types of characteristics of early childhood education students aged 3 to 4 years who have articulation errors: characteristics based on gender and type of articulation error. Keywords: Proportion Estimation, Lower Grade Elementary School Students, Articulation Errors.